Comparative biogeography and ecology of freshwater fishes in the Breede and associated river systems, South Africa - Chakona, Albert (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2012)
Distribution patterns and levels of genetic diversity in extant taxa are a product of complex palaeogeographic processes and climatic oscillations as well as the species' intrinsic ecological adaptations. The Cape Floristic Region of South Africa presents a unique system for studying the processes that promote species diversification and distribution patterns. This region has a high degree of endemism of both terrestrial and aquatic biota and is clearly isolated from neighbouring areas by the Cape Fold Mountains and the Great Escarpment. The objective of this study was to firstly examine the ecology of freshwater fishes belonging to the genera Galaxias, Pseudobarbus and Sandelia in the south-western CFR. This was followed by an assessment of the genetic diversity of these taxa. Unique lineages were identified and their distribution was mapped. The work aimed to explore the role of the region's complex palaeogeographic and climatic history as well as the role of the species' ecological adaptations in driving lineage diversification and shaping contemporary distribution patterns. The four main components of the study can be summarised as follows: 1. Habitat associations of three widely distributed lineages of Galaxias zebratus Pseudobarbus burchelli and Sandelia capensis were evaluated at multiple localities in minimally disturbed mountain tributaries of the Breede, Duiwenhoks and Goukou River systems. The lineages have distinct habitat associations which were related to differences in their morphological traits. The slender-bodied Galaxias 'nebula' and the fusiform-shaped Pseudobarbus 'Breede' are capable of exploiting upper reaches with faster water velocity. By contrast, the laterally compressed Sandelia 'eastern' is restricted to lower reaches, making this lineage more susceptible to a wide array of impacts. 2. A recently discovered lineage of Galaxias zebratus, (Galaxias 'nebula'), was found to be capable of tolerating emersion for a prolonged period of time. This is the first time that such capabilities have been documented in an African galaxiid. These adaptations have implications for the interpretation of Galaxias 'nebula's wide distribution range. 3. The phylogeography of Galaxias 'nebula' across its entire distribution range was investigated using two mitochondrial genes (cytochrome c oxidase subunit I (COI) and cytochrome b (cyt b)). This lineage has a complex evolutionary history that was influenced by both intrinsic and extrinsic factors. Rare events such as episodic drainage connections during Pleistocene and Holocene pluvial periods, possibly augmented by river confluences during periods of lower sea-levels and river capture events seem to be the most credible explanation for the extensive contemporary distribution and the relatively shallow genetic divergence between different river systems. 4. Mitochondrial cyt b sequences were used (i) to assess genetic diversity in G. zebratus, P. burchelli and S. capensis from the south-western CFR and (ii) to determine the roles of intrinsic ecological adaptations and extrinsic landscape and climatic changes in promoting genetic diversification and shaping present day distribution patterns of lineages in the three taxa. Marine incursions during periods of major sea-level transgressions are proposed to have isolated populations in upland refugia, thereby driving allopatric divergence in these species. Subsequent connections of rivers during wetter periods and lower sea-levels are proposed to have facilitated post-speciation dispersal of lineages to attain present day distribution patterns. While detailed morphological studies and further genetic analysis are needed to substantiate the taxonomic status of the newly discovered lineages of Galaxias zebratus, Pseudobarbus burchelli and Sandelia capensis, results of the present study indicate that the south-western CFR represents a previously unrecognised centre of freshwater fish diversity and microendemism in the broader Cape Floristic Region. Accurate identification of lineages and comprehensive mapping of their distribution is a fundamental pre-requisite for ecological studies, assessing conservation status and implementation of appropriate conservation measures.
Keywords: Freshwater fishes -- South Africa -- Breede River; Freshwater fishes -- South Africa -- Geographical distribution; Freshwater fishes -- Ecology; Feshwater fishes -- Genetics